A Qualitative and Systematic Literature Review in Enhancing Maritime Sustainability through Electronic Agreements - Tri Cahyadi; Winarno Winarno; Riyanto Riyanto; April Gunawan Malau (Jurnal Kajian dan Penelitian Umum, 2025)
The increasing complexity of maritime operations and the global push for digitalization have driven the adoption of electronic agreements as a means to enhance legal compliance, operational efficiency, and environmental sustainability. This research investigates the legality and applicability of electronic contracts within the maritime sector, addressing gaps in previous studies by incorporating the perspectives of maritime professionals, educators, and recent graduates. The study aims to explore how electronic agreements can streamline port and shipping management, improve vocational maritime education, and promote sustainable practices. Key research questions focus on the effectiveness of electronic contracts, their integration into maritime curricula, and the operational challenges faced by industry professionals. Using a mixed-methods approach, the research combines a Systematic Literature Review (SLR) with qualitative data from interviews and questionnaires conducted with 10 participants, including experts, lecturers, and graduates. The results reveal a strong alignment between theoretical frameworks and practical applications, with overall indicators scoring 9/10, reflecting high levels of efficiency and acceptance. The findings demonstrate that electronic agreements facilitate faster transactions, reduce administrative costs, and enhance legal clarity. The integration of digital contract management into maritime education further prepares future seafarers for evolving industry demands. This research provides valuable insights for policymakers, educators, and industry leaders, contributing to the advancement of maritime digitalization and sustainability.